Positive electrode active material, secondary battery, and electric device

By introducing boron oxide and carbon cladding into the positive electrode active material of lithium manganese iron phosphate batteries, the battery capacity attenuation, internal resistance growth and gas production problems during circulation are solved, and more stable circulation performance and lower internal resistance and volume expansion rates are achieved.

CN119517959APending Publication Date: 2025-02-25SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411676698.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The capacity of lithium manganese iron phosphate batteries rapidly decay during the middle and late periods of the cycle, the internal resistance increases rapidly, and the intensification of gas production leads to battery swelling. The intrinsic conductivity of the materials is poor and gas production is caused by circulation under high temperature and high voltage conditions.

Method used

A positive electrode active material including a core material and a carbon coating layer is used. The core material is composed of lithium manganese manganese oxide and boron oxide. The boron oxide is distributed between the pores of lithium manganese manganese oxide. The carbon coating layer accounts for 0.2 to 7% of the material mass and the thickness is 2 to 20 nm.

Benefits of technology

It effectively improves circulation stability, reduces internal resistance, suppresses gas production, reduces volume expansion rate, and improves the electrochemical performance of the battery under high temperature and high voltage state.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005148152860000121
    Figure BDA0005148152860000121
  • Figure BDA0005148152860000131
    Figure BDA0005148152860000131
  • Figure BDA0005148152860000141
    Figure BDA0005148152860000141
Patent Text Reader

Abstract

The invention discloses a positive electrode active material, a secondary battery and a power utilization device, and belongs to the technical field of batteries, the positive electrode active material comprises a core material and a carbon coating layer arranged on the outer surface of the core material, the core material comprises a positive electrode material and boron oxide, the boron oxide is at least partially distributed among pores of the positive electrode material, and meanwhile, the positive electrode material contains the manganese-iron-lithium oxide with specific doping elements, so that the lithium ion secondary battery has stable electrochemical capability in a high-temperature and high-voltage state, and therefore, the cycling stability can be effectively improved, the internal resistance can be reduced, gas production can be inhibited, and the service life of the lithium ion secondary battery can be prolonged. The volume expansion rate is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a positive electrode active material, a secondary battery and an electrical device. Background Art

[0002] Long battery life, low cost and high safety have always been important goals for the popularization of new energy power drive solutions. The main measure to solve the problem of long battery life is to develop high-gram capacity and high-voltage lithium battery positive electrode materials. Lithium iron manganese phosphate positive electrode materials came into being. Lithium iron manganese phosphate takes into account the high safety performance of lithium iron phosphate positive electrode materials. Although the theoretical gram capacity is close to 170mAh / g with lithium iron phosphate, due to its high lithium voltage of 4.1V, the energy density of lithium iron manganese phosphate can be increased by 10% to 20% relative to lithium iron phosphate, and the unit watt-hour cost of lithium iron phosphate batteries is estimated to be reduced by 5 to 10% relative to lithium iron phosphate batteries. Due to its low cost, high safety and high voltage characteristics relative to lithium iron phosphate, lithium iron manganese phosphate is expected to become a new power positive electrode active material, and even a potential energy storage positive electrode material.

[0003] At the current stage, the development of lithium manganese iron phosphate has the following problems. As the manganese content increases, the battery shows rapid capacity decay in the middle and late stages of the cycle, the internal resistance increases rapidly, and gas production intensifies, causing battery swelling and other problems. At the same time, the manganese dissolution caused by the Chiang-Taylor effect causes cycle decay, the material's intrinsic conductivity is poor, and there is a gas production problem caused by cycling under high temperature and high voltage conditions.

[0004] In view of this, this application is filed. Summary of the invention

[0005] The purpose of the present application is to overcome the shortcomings of the prior art and provide a positive electrode active material, a secondary battery and an electrical device. The positive electrode active material can effectively improve the cycle stability, reduce the internal resistance, inhibit gas production, and reduce the volume expansion rate.

[0006] To achieve the above-mentioned object, the first aspect of the present application provides a positive electrode active material, comprising a core material and a carbon coating layer disposed on the outer surface of the core material, wherein the core material comprises a positive electrode material and boron oxide, and the boron oxide is at least partially distributed between the pores of the positive electrode material;

[0007] The positive electrode material includes manganese iron lithium oxide, and the manganese iron lithium oxide includes a molecular formula of Li a Mn b Fe c X d Z eA compound of PO4, where b + c + d + e = 1, 0.95 ≤ a ≤ 1.05, 0 < b < 1, 0 < c < 1, 0 ≤ d ≤ 0.1, 0 ≤ e ≤ 0.1, and d and e are not both 0. X contains at least one of Mg, Nb, Mo, Zn, Co, Ni, Cu, and Z contains at least one of Ti, Al, Ce, Cr, V, Ge, Sn.

[0008] As an embodiment of the present application, the mass percentage of the carbon coating layer in the positive electrode active material is 0.2 - 7%.

[0009] As an embodiment of the present application, the thickness of the carbon coating layer is 2 - 20 nm.

[0010] As an embodiment of the present application, the mass percentage of boron oxide in the positive electrode active material is 0.2 - 5%.

[0011] As an embodiment of the present application, at least one of the following (i) - (iv) is satisfied:

[0012] (i) 0.01 ≤ d ≤ 0.05;

[0013] (ii) 0.01 ≤ e ≤ 0.05;

[0014] (iii) 0.9 ≤ b + c < 1;

[0015] (iv) 0.2 ≤ c < 0.3.

[0016] As an embodiment of the present application, X contains Mg and Z contains Ti.

[0017] As an embodiment of the present application, the average particle size of the positive electrode active material is 0.3 - 1.8 μm.

[0018] The second aspect of the present application provides a secondary battery, including a positive electrode sheet, and the positive electrode sheet contains the above-mentioned positive electrode active material.

[0019] As an embodiment of the present application, the sheet resistance of the positive electrode sheet is 395 mΩ or less.

[0020] The third aspect of the present application provides an electrical device, including the above-mentioned secondary battery, and the secondary battery serves as the power supply of the electrical device.

[0021] The beneficial effects of the present application are as follows:

[0022] The inner core of the positive electrode active material of the present application includes a positive electrode material and boron oxide, wherein the boron oxide is at least partially distributed between the pores of the positive electrode material. At the same time, the positive electrode material contains manganese iron lithium oxide with specific doping elements, which ensures that the lithium-ion secondary battery has stable electrochemical capabilities under high temperature and high voltage conditions. The coating of the carbon layer effectively improves the conductivity of the positive electrode active material, can effectively inhibit manganese dissolution, avoid the deposition of Mn elements on the surface of the SEI film, effectively avoid the increase of internal resistance, and thus effectively improve the cycle stability, reduce the internal resistance, inhibit gas production, and reduce the volume expansion rate. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0024] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0025] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0026] The embodiment of the present application provides a positive electrode active material, including a core material and a carbon coating layer disposed on the outer surface of the core material, wherein the core material includes a positive electrode material and boron oxide, and the boron oxide is at least partially distributed between the pores of the positive electrode material;

[0027] The positive electrode material includes manganese iron lithium oxide, and the manganese iron lithium oxide includes a molecular formula of Li a Mn b Fe c X d Z eCompounds of PO4, where b + c + d + e = 1, 0.95 ≤ a ≤ 1.05, 0 < b < 1, 0 < c < 1, 0 ≤ d ≤ 0.1, 0 ≤ e ≤ 0.1, and d and e are not both 0, X contains at least one of Mg, Nb, Mo, Zn, Co, Ni, Cu, and Z contains at least one of Ti, Al, Ce, Cr, V, Ge, Sn.

[0028] The core of the positive electrode active material of this application includes a positive electrode material and boron oxide, and the boron oxide is at least partially distributed between the pores of the positive electrode material. At the same time, the positive electrode material contains manganese iron lithium oxide with specific doping elements, ensuring that the lithium ion secondary battery has stable electrochemical capabilities under high temperature and high voltage conditions. The coating of the carbon layer effectively improves the conductivity of the positive electrode active material, can effectively inhibit the phenomenon of manganese dissolution, avoid the deposition of Mn elements on the surface of the negative electrode SEI film, avoid the increase of internal resistance, thereby improving the cycle stability, reducing the internal resistance, and inhibiting gas generation and reducing the volume expansion rate.

[0029] Specifically, X (X contains at least one of Mg, Nb, Mo, Zn, Co, Ni, Cu) and Z (Z contains at least one of Ti, Al, Ce, Cr, V, Ge, Sn) are doped into the manganese iron lithium oxide. The doping of the elements corresponding to X can replace Fe in the manganese iron lithium oxide 2+ The sites are randomly distributed in the lattice of LMFP to form a solid solution, reducing the unit cell volume of the manganese iron lithium oxide, widening the ion channels adjacent to the X - O bond, thereby improving the lithium ion transport performance and the ionic conductivity of the manganese iron lithium oxide. The doping of the elements corresponding to Z can form a solid solution with Fe 2+ to form a solid solution, reduce the lattice distortion caused by the Jahn - Teller effect, and can also form transition metal - vacancy pairs, improving the dynamic stability of the olivine structure during the cycle and improving the cycle performance.

[0030] In one of the embodiments, the positive electrode material includes manganese iron lithium oxide, and the manganese iron lithium oxide includes a compound with the molecular formula Li a Mn b Fe c X d Z e PO4, where b + c + d + e = 1, 0.95 ≤ a ≤ 1.05, 0 < b < 1, 0 < c < 1, 0 < d ≤ 0.1, 0 < e ≤ 0.1, X contains at least one of Mg, Nb, Mo, Zn, Co, Ni, Cu, and Z contains at least one of Ti, Al, Ce, Cr, V, Ge, Sn.

[0031] In one embodiment, the mass percentage of the carbon coating layer to the positive electrode active material is 0.2-7%, for example, it can be 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7% or a range consisting of any two of these values. By controlling the mass percentage of the coating layer within this range, the conductivity can be further improved, the manganese dissolution phenomenon can be improved, and the cycle performance can be more effectively improved and the internal resistance can be reduced.

[0032] In one embodiment, the mass percentage of the carbon coating layer to the positive electrode active material is 1-2%. The present application can further improve the cycle stability and reduce the internal resistance by controlling the mass percentage of the coating layer within this range.

[0033] In one embodiment, the thickness of the carbon coating layer is 2 to 20 nm, for example, it can be 2 nm, 3 nm, 4 nm, 8 nm, 10 nm, 12 nm, 14 nm, 16 nm, 18 nm, 20 nm or a range consisting of any two of the values. The present application controls the thickness of the coating layer to 2 to 20 nm, which can effectively improve the structural stability of the positive electrode active material, effectively provide an ion transmission channel, and reduce the ion transmission distance, which can further improve the cycle stability and reduce the internal resistance.

[0034] In one embodiment, the mass percentage of the boron oxide in the positive electrode active material is 0.2-5%, for example, it can be 0.2%, 0.5%, 1%, 2%, 3%, 4%, 5% or a range consisting of any two of these values. By controlling the mass percentage of boron oxide in the positive electrode active material, the boron oxide can be reasonably distributed between the pores and inside the positive electrode material, effectively improving the structural stability, inhibiting gas production, preventing the breakage and loss of LMFP particles during the charge and discharge process, and ensuring that the lithium-ion secondary battery has stable electrochemical capabilities under high temperature and high voltage conditions.

[0035] In one embodiment, the mass percentage of boron oxide in the positive electrode active material is 1-2%. By controlling the mass percentage of boron oxide in the positive electrode active material within this range, the structural stability can be further improved and gas production can be suppressed, thereby ensuring that the lithium-ion secondary battery has stable electrochemical capabilities under high temperature and high voltage conditions.

[0036] In one embodiment, at least one of the following (i) to (iv) is satisfied:

[0037] (i) 0.01≤d≤0.05;

[0038] (ii) 0.01≤e≤0.05;

[0039] (iii) 0.9≤b+c<1;

[0040] (iv)0.2≤c<0.3.

[0041] By controlling the values ​​of d, e, c and the value of b+c, the conductivity can be further improved, gas generation can be suppressed, and cycle stability can be improved.

[0042] In one embodiment, c+d+e≤0.3.

[0043] In one embodiment, X comprises Mg and / or Co, and Z comprises Ti and / or Al. In one embodiment, X comprises Mg, and Z comprises Ti. When the manganese iron lithium oxide is doped with the above elements at the same time, the cycle performance and gas generation performance of the lithium ion secondary battery at high temperature can be further improved.

[0044] In one embodiment, the average particle size of the positive electrode active material is 0.3 to 1.8 μm, for example, it can be 0.3 μm, 0.5 μm, 0.6 μm, 0.8 μm, 1 μm, 1.2 μm, 1.5 μm, 1.8 μm or a range consisting of any two of these values. By controlling the average particle size of the positive electrode active material, the active sites can be effectively increased, the contact area between the positive electrode plate and the electrolyte can be increased, the polarization effect can be reduced, and the cycle stability can be improved and the gas production of the electrolyte side reaction can be inhibited.

[0045] In one embodiment, the average particle size of the positive electrode active material is 0.5-1 μm.

[0046] In one embodiment, the preparation method of the positive electrode active material is:

[0047] The manganese iron lithium oxide precursor, carbon source, boron source and binder are mixed evenly, water is added, stirred, dried, rolled, granulated, crushed, sieved, sintered in an air atmosphere, sintered in a nitrogen atmosphere, and sieved to obtain a positive electrode active material.

[0048] In one embodiment, the carbon source includes at least one of glucose, sucrose, citric acid, stearic acid, polyethylene glycol, starch, and cellulose.

[0049] In one embodiment, the boron source includes at least one of boric acid and boron oxide.

[0050] In one embodiment, the binder includes at least one of PTFE emulsion, carboxymethyl cellulose, polyacrylic acid, lithium polyacrylate, and styrene-butadiene rubber.

[0051] In one embodiment, the mass ratio of the manganese iron lithium oxide precursor, the carbon source, the boron source, and the binder is (93-99): (0.1-3): (0.1-1): (0.2-3).

[0052] In one embodiment, the amount of water added is 11-40% of the total mass of the manganese iron lithium oxide precursor, the carbon source, the boron source, and the binder.

[0053] In one embodiment, the sintering temperature in air atmosphere is 200-250° C., and the sintering time is 0.5-2 h.

[0054] In one embodiment, the sintering temperature in a nitrogen atmosphere is 600-850° C., and the sintering time is 6-12 hours.

[0055] In one embodiment, after sintering in a nitrogen atmosphere, screening is performed to obtain a positive electrode active material with a desired particle size.

[0056] In one embodiment, the preparation method of the manganese iron lithium oxide precursor is: according to the molecular formula of manganese iron lithium oxide, the ingredients are prepared, the lithium source, manganese source, iron source, X source, and Z source are prepared according to Li: Mn: Fe: X: Z: PO4 = a: b: c: d: e: 1, and mixed evenly to obtain the manganese iron lithium oxide lithium precursor.

[0057] In one embodiment, the lithium source includes at least one of lithium carbonate, lithium nitrate, lithium oxalate, lithium hydroxide, and lithium dihydrogen phosphate.

[0058] In one embodiment, the manganese source includes at least one of manganese chloride, manganese oxalate, manganese carbonate, manganese acetate, manganese nitrate, and manganese sulfate.

[0059] In one embodiment, the iron source includes at least one of ferrous hydroxide, ferrous sulfate, ferrous oxalate, ferric nitrate, and ferrous chloride.

[0060] In one embodiment, the phosphorus source includes at least one of diammonium phosphate, diammonium hydrogen phosphate, and phosphoric acid.

[0061] In one embodiment, the X source includes at least one of sulfate, nitrate, acetate and chloride containing X.

[0062] In one embodiment, the Z source includes at least one of sulfate, nitrate, acetate and chloride containing Z.

[0063] An embodiment of the present application provides a secondary battery, including a positive electrode plate, wherein the positive electrode plate contains the positive electrode active material described above.

[0064] More specifically, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, and the positive electrode active material layer includes the positive electrode active material mentioned above.

[0065] In one embodiment, the film resistance of the positive electrode sheet is less than 395 mΩ.

[0066] In the present application, the type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. In one embodiment, the positive electrode current collector includes metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper. In one embodiment, the positive electrode current collector is a metal material. In one embodiment, the positive electrode current collector is aluminum.

[0067] There is no particular restriction on the form of the positive electrode current collector. When the positive electrode current collector is a metal material, the positive electrode current collector may be in the form of metal foil, metal cylinder, metal strip roll, metal plate, metal foil, metal plate mesh, stamped metal, foamed metal, etc. When the positive electrode current collector is a carbon material, the positive electrode current collector may include but is not limited to a carbon plate, a carbon film, a carbon cylinder, etc.

[0068] In one embodiment, the positive electrode material layer further includes a conductive agent and a binder.

[0069] In one embodiment, the secondary battery further includes a negative electrode plate, wherein the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material.

[0070] In the present application, there is no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, it can be copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector.

[0071] In one embodiment, the negative electrode active material can be natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithium titanate Li4Ti5O 12 , at least one of Li-Al alloy and metallic lithium.

[0072] In one embodiment, the negative electrode active material layer further includes a conductive agent and a binder.

[0073] In one embodiment, the type of the conductive agent mentioned in the present application is not limited, and any known conductive agent can be used.

[0074] In one embodiment, the conductive agent includes at least one of carbon materials such as acetylene black, needle coke, carbon nanotubes, and graphene.

[0075] In one embodiment, the type of the binder mentioned in the present application is not limited, and any known positive electrode binder can be used.

[0076] In one embodiment, the binder includes at least one of polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, nitrocellulose, styrene-butadiene rubber, nitrile rubber, fluororubber, isoprene rubber, polybutadiene rubber, ethylene-propylene rubber, polyvinylidene fluoride, polytetrafluoroethylene, and fluorinated polyvinylidene fluoride.

[0077] In the secondary battery mentioned in the present application, a separator is usually provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator are not particularly limited as long as the effect of the present application is not significantly impaired.

[0078] In one embodiment, the separator includes a porous sheet or non-woven fabric having excellent liquid retention. The materials of the resin or glass fiber separator include, but are not limited to, polyolefin, aromatic polyamide, polytetrafluoroethylene, polyethersulfone, and the like.

[0079] In one embodiment, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above-mentioned diaphragm can be used alone or in any combination.

[0080] In some embodiments, the secondary battery comprises an electrolyte, and the type of the electrolyte is not subject to specific restrictions. The electrolyte comprises an electrolyte salt and an organic solvent, and the specific types of the electrolyte salt and the organic solvent are not subject to specific restrictions and can be selected according to actual needs. The electrolyte may also include additives, and the types of the additives are not particularly limited. They may be film-forming additives for the positive electrode and / or the negative electrode, or additives that can improve certain properties of the battery, such as additives that improve the high or low temperature performance of the battery.

[0081] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.

[0082] An embodiment of the present application provides an electric device, comprising the secondary battery described above, wherein the secondary battery serves as a power supply for the electric device.

[0083] Exemplarily, the above-mentioned electrical devices may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto.

[0084] The present application is further described below with specific embodiments:

[0085] Example 1

[0086] A method for preparing a positive electrode active material comprises the following steps:

[0087] (1) lithium carbonate, manganese acetate, ferrous oxalate, magnesium oxide, and ammonium dihydrogen phosphate were weighed and mixed uniformly in a molar ratio of Li:Mn:Fe:Mg:PO4=1:0.7:0.29:0.01:1 to obtain a manganese iron lithium oxide precursor;

[0088] (2) The manganese iron lithium oxide precursor, glucose, boric acid, and polyacrylic acid are mixed uniformly in a mass ratio of 95:2:1:2, water is added (the amount of water added is 30% of the total mass of the manganese iron lithium oxide precursor, glucose, boric acid, and polyacrylic acid), stirred, dried, rolled, granulated, crushed, sieved, sintered at 200° C. for 1 h in an air atmosphere, sintered at 650° C. for 8 h in a nitrogen atmosphere, and sieved to obtain a positive electrode active material.

[0089] The positive electrode active material of this embodiment includes a core material and a carbon coating layer arranged on the outer surface of the core material, the core material includes a positive electrode material and boron oxide, the boron oxide is at least partially distributed between the pores of the positive electrode material, and the molecular formula of the positive electrode material is LiMn 0.7 Fe 0.29 Mg 0.01 PO4.

[0090] In this embodiment, the mass percentage of boron oxide in the positive electrode active material is 1%, and the mass percentage of the carbon coating layer in the positive electrode active material is 2%.

[0091] The thickness of the carbon coating layer is 7 nm.

[0092] Embodiments 2 to 4

[0093] The difference between Examples 2 to 4 and Example 1 is that Examples 2 to 4 adjust the mass percentage of boron oxide in the positive electrode active material by changing the amount of boric acid added (the amount of glucose added remains unchanged).

[0094] Embodiments 5 to 7

[0095] The difference between Examples 5 to 7 and Example 1 is that Examples 5 to 7 adjust the mass percentage of the carbon coating layer in the positive electrode active material and the thickness of the carbon coating layer by changing the amount of glucose added (the amount of boric acid added remains unchanged).

[0096] Embodiments 8 to 10

[0097] The difference between Examples 8 to 10 and Example 1 is that Examples 8 to 10 adjust the average particle size of the positive electrode active material by adjusting the screening after sintering.

[0098] Examples 11-12

[0099] The difference between Examples 11 and 12 and Example 1 is that Examples 11 and 12 adjust the amount of Mg added by changing the amount of magnesium oxide added.

[0100] Embodiment 13

[0101] The difference between Example 13 and Example 11 is that an equimolar amount of cobalt oxide is used to replace magnesium oxide.

[0102] Embodiment 14

[0103] A method for preparing a positive electrode active material comprises the following steps:

[0104] (1) lithium carbonate, manganese acetate, ferrous oxalate, titanium oxide, and ammonium dihydrogen phosphate were weighed and mixed evenly in a molar ratio of Li:Mn:Fe:Ti:PO4=1:0.7:0.29:0.01:1 to obtain a manganese iron lithium oxide precursor;

[0105] (2) The manganese iron lithium oxide precursor, glucose, boric acid, and polyacrylic acid are mixed uniformly in a mass ratio of 95:2:1:2, water is added (the amount of water added is 30% of the total mass of the manganese iron lithium oxide precursor, glucose, boric acid, and polyacrylic acid), stirred, dried, rolled, granulated, crushed, sieved, sintered at 200° C. for 1 h in an air atmosphere, sintered at 650° C. for 8 h in a nitrogen atmosphere, and sieved to obtain a positive electrode active material.

[0106] The positive electrode active material of this embodiment includes a core material and a carbon coating layer arranged on the outer surface of the core material, the core material includes a positive electrode material and boron oxide, the boron oxide is at least partially distributed between the pores of the positive electrode material, and the molecular formula of the positive electrode material is LiMn 0.7 Fe 0.29 Ti 0.01 PO4.

[0107] In this embodiment, the mass percentage of boron oxide in the positive electrode active material is 1%, and the mass percentage of the carbon coating layer in the positive electrode active material is 2%.

[0108] The thickness of the carbon coating layer is 7 nm.

[0109] Embodiments 15-16

[0110] The difference between Examples 15 and 16 and Example 14 is that Examples 15 and 16 adjust the amount of Ti added by changing the amount of titanium oxide added.

[0111] Embodiment 17

[0112] The difference between Example 17 and Example 15 is that an equal molar amount of aluminum oxide is used to replace titanium oxide.

[0113] Embodiment 18

[0114] A method for preparing a positive electrode active material comprises the following steps:

[0115] (1) lithium carbonate, manganese acetate, ferrous oxalate, magnesium oxide, titanium oxide, and ammonium dihydrogen phosphate were weighed and mixed uniformly in a molar ratio of Li:Mn:Fe:Mg:Ti:PO4=1:0.7:0.28:0.01:0.01:1 to obtain a manganese iron lithium oxide precursor;

[0116] (2) The manganese iron lithium oxide precursor, glucose, boric acid, and polyacrylic acid are mixed uniformly in a mass ratio of 95:2:1:2, water is added (the amount of water added is 30% of the total mass of the manganese iron lithium oxide precursor, glucose, boric acid, and polyacrylic acid), stirred, dried, rolled, granulated, crushed, sieved, sintered at 200° C. for 1 h in an air atmosphere, sintered at 650° C. for 8 h in a nitrogen atmosphere, and sieved to obtain a positive electrode active material.

[0117] The positive electrode active material of this embodiment includes a core material and a carbon coating layer arranged on the outer surface of the core material, the core material includes a positive electrode material and boron oxide, the boron oxide is at least partially distributed between the pores of the positive electrode material, and the molecular formula of the positive electrode material is LiMn 0.7 Fe 0.28 Mg 0.01 Ti 0.01 PO4.

[0118] In this embodiment, the mass percentage of boron oxide in the positive electrode active material is 1%, and the mass percentage of the carbon coating layer in the positive electrode active material is 2%.

[0119] The thickness of the carbon coating layer is 7 nm.

[0120] Embodiments 19 to 20

[0121] The difference between Examples 19 to 20 and Example 18 is that Examples 19 to 20 adjust the addition amounts of Mg and Ti by changing the addition amounts of magnesium oxide and titanium oxide.

[0122] Comparative Example 1

[0123] A method for preparing a positive electrode active material comprises the following steps:

[0124] (1) lithium carbonate, manganese acetate, ferrous oxalate, and ammonium dihydrogen phosphate were weighed and mixed evenly in a molar ratio of Li:Mn:Fe:PO4=1:0.7:0.3:1 to obtain a manganese iron lithium oxide precursor;

[0125] (2) The manganese iron lithium oxide precursor, glucose, boric acid, and polyacrylic acid are mixed uniformly in a mass ratio of 95:2:1:2, water is added (the amount of water added is 30% of the total mass of the manganese iron lithium oxide precursor, glucose, boric acid, and polyacrylic acid), stirred, dried, rolled, granulated, crushed, sieved, sintered at 200° C. for 1 h in an air atmosphere, sintered at 650° C. for 8 h in a nitrogen atmosphere, and sieved to obtain a positive electrode active material.

[0126] The positive electrode active material of this embodiment includes a core material and a carbon coating layer arranged on the outer surface of the core material, the core material includes a positive electrode material and boron oxide, the boron oxide is at least partially distributed between the pores of the positive electrode material, and the molecular formula of the positive electrode material is LiMn 0.7 Fe 0.3 PO4.

[0127] In this embodiment, the mass percentage of boron oxide in the positive electrode active material is 1%, and the mass percentage of the carbon coating layer in the positive electrode active material is 2%.

[0128] The thickness of the carbon coating layer is 7 nm.

[0129] Comparative Example 2

[0130] A method for preparing a positive electrode active material comprises the following steps:

[0131] (1) lithium carbonate, manganese acetate, ferrous oxalate, and ammonium dihydrogen phosphate were weighed and mixed evenly in a molar ratio of Li:Mn:Fe:Mg:PO4=1:0.7:0.1:0.2:1 to obtain a manganese iron lithium oxide precursor;

[0132] (2) The manganese iron lithium oxide precursor, glucose, boric acid, and polyacrylic acid are mixed uniformly in a mass ratio of 95:2:1:2, water is added (the amount of water added is 30% of the total mass of the manganese iron lithium oxide precursor, boric acid, and polyacrylic acid), stirred, dried, rolled, granulated, crushed, sieved, sintered at 200° C. for 1 h in an air atmosphere, sintered at 650° C. for 8 h in a nitrogen atmosphere, and sieved to obtain a positive electrode active material.

[0133] The positive electrode active material of this embodiment includes a core material and a carbon coating layer arranged on the outer surface of the core material, the core material includes a positive electrode material and boron oxide, the boron oxide is at least partially distributed between the pores of the positive electrode material, and the molecular formula of the positive electrode material is LiMn 0.7 Fe 0.1 Mg 0.2 PO4.

[0134] In this embodiment, the mass percentage of boron oxide in the positive electrode active material is 1%, and the mass percentage of the carbon coating layer in the positive electrode active material is 2%.

[0135] The thickness of the carbon coating layer is 7 nm.

[0136] Comparative Example 3

[0137] A method for preparing a positive electrode active material comprises the following steps:

[0138] (1) lithium carbonate, manganese acetate, ferrous oxalate, magnesium oxide, and ammonium dihydrogen phosphate were weighed and mixed evenly in a molar ratio of Li:Mn:Fe:Mg:PO4=1:0.7:0.29:0.01:1 to obtain a manganese iron lithium oxide precursor;

[0139] (2) The manganese iron lithium oxide precursor, glucose, and polyacrylic acid are mixed uniformly in a mass ratio of 95.5:2.5:2, water is added (the amount of water added is 30% of the total mass of the manganese iron lithium oxide precursor, glucose, and polyacrylic acid), stirred, dried, rolled, granulated, crushed, sieved, sintered at 200° C. for 1 h in an air atmosphere, sintered at 650° C. for 8 h in a nitrogen atmosphere, and sieved to obtain a positive electrode active material.

[0140] The positive electrode active material of this embodiment includes a core material and a carbon coating layer arranged on the outer surface of the core material, wherein the core material includes a positive electrode material, and the molecular formula of the positive electrode material is LiMn 0.7 Fe 0.29 Mg 0.01 PO4.

[0141] The carbon coating layer accounts for 2% by mass of the positive electrode active material.

[0142] The thickness of the carbon coating layer is 7 nm.

[0143] Table 1

[0144]

[0145]

[0146] Test Case

[0147] The positive electrode active materials prepared in each embodiment and comparative example are assembled into a secondary battery, and the preparation method is as follows:

[0148] (1) Preparation of positive electrode sheet: According to the weight ratio of positive electrode active material: conductive agent SP: binder PDVF = 96:2:2, NMP was used as solvent and stirred to disperse into a uniform slurry, and then coated on 14μm aluminum foil with a coating load weight of 250g / m 2 After double-sided coating and drying, the film is rolled into a thickness of 230μm and then cut into positive electrode sheets for use. The cut positive electrode sheets are taken and the diaphragm resistance of the positive electrode sheets is tested using a four-probe diaphragm internal resistance tester.

[0149] (2) Battery assembly: Graphite is used as the negative electrode material. According to the weight ratio of negative electrode material graphite: conductive agent SP: binder CMC = 96:2:2, water is used as solvent and stirred to disperse into a uniform slurry, which is then coated on copper foil. After drying, it is rolled and cut into negative electrode sheets for use. The cut positive and negative electrode sheets are separated by diaphragms, wound together and loaded into aluminum-plastic film. After drying to remove moisture from the sheets, liquid is injected in a drying room, and then heat-sealed to form a battery.

[0150] After the battery has gone through the steps of formation and capacity division, the discharge capacity and initial efficiency of the battery are obtained. The initial volume V0 of the battery is measured by the drainage method, and then the battery is transferred to an oven at 45°C and cycled according to the upper limit voltage range (2.5-4.4V). After 500 cycles of 1C / 1C charge and discharge, the battery volume V1 is measured again. The battery volume expansion rate is obtained according to the following formula. The results are shown in Table 2.

[0151] Volume expansion rate = (V1-V0) / V0*100%

[0152] Capacity retention rate = first cycle capacity / capacity after 500 cycles * 100%

[0153] Table 2

[0154]

[0155]

[0156] It can be seen from the examples and comparative examples of the present application that the positive electrode active material described in the present application can effectively improve cycle stability, reduce internal resistance, inhibit gas production, and reduce volume expansion rate.

[0157] From the comparison of Examples 1 to 4, it can be seen that the present application effectively improves the cycle stability, reduces the internal resistance, inhibits gas production, and reduces the volume expansion rate by controlling the mass percentage of boron oxide in the positive electrode active material to 0.2 to 5%. By controlling the mass percentage of boron oxide in the positive electrode active material to 1 to 2%, the cycle stability is further improved, the internal resistance is reduced, the gas production is inhibited, and the volume expansion rate is reduced.

[0158] By comparing Examples 1 and 5 to 7, it can be seen that the present invention further improves the cycle stability, reduces the internal resistance, inhibits gas generation, and reduces the volume expansion rate by controlling the thickness of the carbon coating layer to 2 to 20 nm and the content of the carbon coating layer to 0.2 to 7%.

[0159] By comparing Examples 1, 8 to 10, it can be seen that the present invention further improves cycle stability, reduces internal resistance, inhibits gas generation, and reduces volume expansion rate by controlling the average particle size of the positive electrode active material to 0.3 to 1.8 μm.

[0160] By comparing Example 1 with Examples 11 to 20, it can be seen that by simultaneously doping the X element and the Z element, the cycle stability is further improved, the internal resistance is reduced, the gas generation is suppressed, and the volume expansion rate is reduced.

[0161] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A positive electrode active material, characterized in that: It comprises a core material and a carbon coating layer arranged on the outer surface of the core material, wherein the core material comprises a positive electrode material and boron oxide, and the boron oxide is at least partially distributed between the pores of the positive electrode material; The positive electrode material includes lithium manganese iron oxide, and the lithium manganese iron oxide includes a compound with the molecular formula Li a Mn b Fe c X d Z e PO4, where b + c + d + e = 1, 0.95 ≤ a ≤ 1.05, 0 < b < 1, 0 < c < 1, 0 ≤ d ≤ 0.1, 0 ≤ e ≤ 0.1, and d and e are not both 0, X includes at least one of Mg, Nb, Mo, Zn, Co, Ni, Cu, and Z includes at least one of Ti, Al, Ce, Cr, V, Ge, Sn.

2. The positive electrode active material according to claim 1, characterized in that The mass percentage of the carbon coating layer to the positive electrode active material is 0.2-7%.

3. The positive electrode active material according to claim 1, characterized in that The thickness of the carbon coating layer is 2-20 nm.

4. The positive electrode active material according to claim 1, characterized in that The mass percentage of the boron oxide in the positive electrode active material is 0.2-5%.

5. The positive electrode active material according to claim 1, characterized in that Satisfy at least one of the following (i) to (iv): (i) 0.01≤d≤0.05; (ii) 0.01≤e≤0.05; (iii) 0.9≤b+c<1; (iv)0.2≤c<0.

3.

6. The positive electrode active material according to claim 1, characterized in that The X includes Mg, and Z includes Ti.

7. The positive electrode active material according to claim 1, characterized in that The average particle size of the positive electrode active material is 0.3 to 1.8 μm.

8. A secondary battery, characterized in that: The invention comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 7.

9. The secondary battery according to claim 8, characterized in that: The film resistance of the positive electrode plate is less than 395 mΩ.

10. An electrical device, characterized in that: It comprises the secondary battery as claimed in claim 8 or 9, wherein the secondary battery is used as a power supply for the electrical device.

Citation Information

Cited By

  • Lithium ion battery, positive electrode active material and preparation method therefor, and electric device

    WO2026179414A1